2014
DOI: 10.1007/s00441-014-1961-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RhoA/ROCK in insulin secretion of pancreatic β-cells in 3D culture

Abstract: Cell-cell contacts and interactions between pancreatic β-cells and/or other cell populations within islets are essential for cell survival, insulin secretion, and functional synchronization. Three-dimensional (3D) culture systems supply the ideal microenvironment for islet-like cluster formation and functional maintenance. However, the underlying mechanisms remain unclear. In this study, mouse insulinoma 6 (MIN6) cells were cultured in a rotating 3D culture system to form islet-like aggregates. Glucose-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Indeed, we found that loss of ROCKII, but not ROCKI, is sufficient to induce the generation and maturation of pancreatic beta-like cells. Although not studied in the context of hESC differentiation, previous studies using rat islets and MIN6 cells are consistent with our finding, suggesting that ROCK inhibitors promote glucose-stimulated insulin secretion 26 , 27 . ROCK signalling has been suggested to function downstream of glucagon-like peptide 1 to rescue glucotoxicity-induced stress fibers 28 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, we found that loss of ROCKII, but not ROCKI, is sufficient to induce the generation and maturation of pancreatic beta-like cells. Although not studied in the context of hESC differentiation, previous studies using rat islets and MIN6 cells are consistent with our finding, suggesting that ROCK inhibitors promote glucose-stimulated insulin secretion 26 , 27 . ROCK signalling has been suggested to function downstream of glucagon-like peptide 1 to rescue glucotoxicity-induced stress fibers 28 .…”
Section: Discussionsupporting
confidence: 91%
“…RhoA is a member of Rho family of GTPases involved in regulating intracellular actin dynamics ( 36 ). It has been demonstrated that RhoA participates in regulating secretion of insulin ( 37 ), and is associated with insulin resistance via phosphorylation of insulin receptor substrate-1 ( 38 ). Moreover, it also mediates adrenocorticotropin-stimulated cortisol biosynthesis in human adrenocortical cells ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated Cdc42 and Rac1 GTPases as well as their effector protein PAK1, the GEF protein Tiam1, and RhoGDI as particularly important for glucose-stimulated insulin secretion in vivo and in vitro in mouse β-cells [6] , [13] , [16] , [17] , [18] , [19] . The Rho-ROCK pathway has also been implicated in β-cell function and insulin secretion [17] , [20] , [21] . For instance, pharmacological inhibition of Rho and ROCK leads to a significant increase in actin depolymerization and GSIS in rat primary β-cells and mouse insulinoma 6 (MIN6) cells [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%